# If x = 2 i

We have,

f (x) = 2x2 – 3x + 7a

Put x = 2

f (2) = 2 (2)2 – 3 (2) + 7a

= 2 * 4 – 6 + 7a

= 8 – 6 + 7a

= 2 + 7a

Given, x = 2 is a root of f (x) = 2x2 – 3x + 7a

f (2) = 0

Therefore, 2 + 7a = 0

7a = -2

a =

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Master the Art of Writing Chemical Formulae42 mins
Combinations of Solids43 mins
Law of Gravitation40 mins
Newton's Second Law46 mins
Quick Recap of Cell62 mins
Circles- All kinds of Questions36 mins
Master Mole Concept in 45 Minutes48 mins
Arc of Circle And Related IMP Qs40 mins
Surface Area and Volume of solids Revision43 mins
Variation in g with Rotation of Earth42 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

Zero of the polynRS Aggarwal & V Aggarwal - Mathematics

If 2 and -1/3 areRS Aggarwal & V Aggarwal - Mathematics

If (x + 1) is a fRS Aggarwal & V Aggarwal - Mathematics

If (x2RS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

If p(x) = x3RS Aggarwal & V Aggarwal - Mathematics

If p(x) = (xRS Aggarwal & V Aggarwal - Mathematics

The coefficient oRS Aggarwal & V Aggarwal - Mathematics